Pendewasaan Demokrasi Melalui Upaya Revitalisasi Lembaga Yudikatif Dalam Pembentukan Badan Peradilan Khusus Pemilihan Kepala Daerah - Haq, Zul Amirul (Jurnal Konstitusi & Demokrasi, 2023)
General elections for regional heads are one of the democratic parties that involve the community directly to elect their leaders. Regional head general election is a political event to determine who the Governor, Mayor and Regent will lead the area. So that in its implementation it is inseparable from various kinds of legal issues which result in a political dispute that must be resolved properly and correctly. The settlement of election disputes, which so far is still gray in nature, will give rise to prolonged ambiguity. So that an effort is needed to revitalize the judiciary as a special judiciary body for regional elections as a manifestation of the country's seriousness in strengthening democracy